2005
DOI: 10.2139/ssrn.871173
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Industry Classification Schemes on Financial Research

Abstract: This paper investigates industry classification systems. During the last 50 years there has been a considerable discussion of problems regarding the classification of economic data by industries. From my perspective, the central point of each classification is to determine a balance between aggregation of similar firms and differentiation between industries. This paper examines the structure and content of industrial classification schemes and how they affect financial research. I use classification systems pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…The industry usually classifies products and enterprises by various classification standards, such as the SIC, ICB, and NAICS (Pierce and Schott, 2012). This application of information studies in economics is also the starting point for many economic studies (Weiner, 2005). Boettcher (1999) noted that the NAICS has made a significant contribution to industrial classification and compared the differences between the NAICS and SIC in the study, noting that the NAICS guarantees the integrity of the classification system from the perspective of multisource data.…”
Section: Industry Taxonomymentioning
confidence: 99%
“…The industry usually classifies products and enterprises by various classification standards, such as the SIC, ICB, and NAICS (Pierce and Schott, 2012). This application of information studies in economics is also the starting point for many economic studies (Weiner, 2005). Boettcher (1999) noted that the NAICS has made a significant contribution to industrial classification and compared the differences between the NAICS and SIC in the study, noting that the NAICS guarantees the integrity of the classification system from the perspective of multisource data.…”
Section: Industry Taxonomymentioning
confidence: 99%
“…The GICS classification structure comprises 10 broad economic sectors aggregated from 23 industry groups, 59 industries, and 122 sub-industries. We selected GISC over other available classification mechanisms such as SIC and NAIC because it outperforms others in explaining financial ratios and lowering valuation errors (Bhojraj, Lee, & Oler, 2003;Weiner, 2005). Given we focus on financial performance ratios and their use in IS research (Chang, Jackson, & Grover, 2003;Du, Huai, & Liu, 2006;Martin & Mykytyn, 2009;Mojsilovic, Ray, Lawrence, & Takriti, 2007;Schumaker & Chen, 2010;Shu, 2010), adopting GISC seems appropriate.…”
Section: Control Groupmentioning
confidence: 99%
“…Given we focus on financial performance ratios and their use in IS research (Chang, Jackson, & Grover, 2003;Du, Huai, & Liu, 2006;Martin & Mykytyn, 2009;Mojsilovic, Ray, Lawrence, & Takriti, 2007;Schumaker & Chen, 2010;Shu, 2010), adopting GISC seems appropriate. While we chose GICS over SIC (Bhojraj et al, 2003;Martin & Mykytyn, 2009;Weiner, 2005) and, therefore, differ from Santhanam and Hartono (2003), we did adopt the general approach of both Santhanam and Hartono (2003) and Martin and Mykytn (2009) in testing our hypotheses at two levels of the classification system (sub-industry and industry group) to strengthen the findings. Table 2 shows the final list of GICS sub-industries and industry groups whose firm members we included as control firms in testing our multi-level hypotheses based on the mapping of IT-ISAC firms to the most granular classification category (GICS sub-industries).…”
Section: Control Groupmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of industry classification systems have been adopted for defining stock affiliation, such as the Standard Industrial Classification, the Global Industry Classification System and the Fama and French [18] system. Weiner [19] evaluated several industrial classification schemes, and found a number of drawbacks for each one. On the other hand, a significant amount of statistical classification models have been applied to common stock analysis, in the areas including common stock investment categories, price-earnings and return-risk equity classification, information content and return performance, and capital structure [20].…”
Section: Introductionmentioning
confidence: 99%